2013
DOI: 10.1002/zaac.201200534
|View full text |Cite
|
Sign up to set email alerts
|

Comments on Peierls‐distorted Indium Chains in In4Se3–x

Abstract: Nominal In4Se3–x with x = 0.65, derived from the prototype compound In4Se3, is a good thermoelectric material achieving a Z value of 1.48 at 705 K. This value is close to state of the art thermoelectric materials. In literature this special behavior is explained by a Peierls‐distortion or Charge Density Wave within the compound caused by the selenium deficit. While extensive thermoelectric studies for different compositions are reported in literature, a solid proof of the existence of selenium deficit samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…Therefore, a distortion leading to a superstructure is not expected for stoichiometric In 4 Se 3 . This is entirely consistent with the structural study of Osters and coworkers 33 , who found no evidence of a Peierls-distortion or a CDW in stoichiometric In 4 Se 3 . It is also noticeable that the frequency of the acoustic modes is very low, suggesting that the bonding is soft with a substantial number of low-frequency optical modes, close in energy to the acoustic modes.…”
Section: Elastic Propertiessupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, a distortion leading to a superstructure is not expected for stoichiometric In 4 Se 3 . This is entirely consistent with the structural study of Osters and coworkers 33 , who found no evidence of a Peierls-distortion or a CDW in stoichiometric In 4 Se 3 . It is also noticeable that the frequency of the acoustic modes is very low, suggesting that the bonding is soft with a substantial number of low-frequency optical modes, close in energy to the acoustic modes.…”
Section: Elastic Propertiessupporting
confidence: 93%
“…The different nature of the bonding of In4 is reflected in its considerably larger atomic displacement parameter than those for the (In 3 ) 5+ cation found in the covalent layers, evident in single-crystal diffraction studies 33 . For instance, the atomic displacement parameter for In4 found by Osters and coworkers 33 is 60% larger than those in the (In 3 ) 5+ cation.…”
Section: Structure and Bondingmentioning
confidence: 95%
See 2 more Smart Citations
“…It indicates that possible deviation from stoichiometry is very small. This result is consistent with those of Osters et al 26 The presence of In as the second phase in the In 4 Se 3 matrix of composite samples was confirmed by DSC analysis (Fig. 5), and SEM + EDX observations (Fig.…”
Section: Electrical and Thermal Transport Propertiessupporting
confidence: 92%